2020
DOI: 10.1002/cam4.3272
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life outcomes from a randomized controlled trial of patient navigation in Latina breast cancer survivors

Abstract: Introduction Breast cancer survivorship is a life‐long process involving challenges to health‐care communities and individuals, especially Latinas. Patient Navigation has shown some success in meeting these challenges. The purpose of this study was to compare the effects of an enhanced Patient Navigation program (Intervention; PN+) vs Control (PN) over time on general cancer and breast cancer‐specific quality of life (QoL) in Latina breast cancer survivors (BCS). Methods We conducted a 2‐year, two‐arm randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…38 Although the analysis of pooled data from the Patient Navigation Research Program sites did not show any difference in quality of life, a smaller randomized trial showed that women who received a nurse navigator intervention after diagnosis had significantly greater satisfaction and rehabilitation and experienced lower levels of distress, anxiety, and depression. 39 Several studies have sought to examine the effect of patient navigation on receipt of treatment after diagnosis. Although these data have been mixed, Ramirez et al 40 reported that a significantly higher percentage of Hispanic and Latinx women assigned to a culturally tailored navigation intervention initiated treatment within 30 days (69.0% vs. 46.3%; p , .05) and 60 days (97.6% vs. 73.1%; p , .001) and experienced a significantly reduced time to treatment (mean, 22.2 days vs. 48.3 days) compared with controls.…”
Section: Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Although the analysis of pooled data from the Patient Navigation Research Program sites did not show any difference in quality of life, a smaller randomized trial showed that women who received a nurse navigator intervention after diagnosis had significantly greater satisfaction and rehabilitation and experienced lower levels of distress, anxiety, and depression. 39 Several studies have sought to examine the effect of patient navigation on receipt of treatment after diagnosis. Although these data have been mixed, Ramirez et al 40 reported that a significantly higher percentage of Hispanic and Latinx women assigned to a culturally tailored navigation intervention initiated treatment within 30 days (69.0% vs. 46.3%; p , .05) and 60 days (97.6% vs. 73.1%; p , .001) and experienced a significantly reduced time to treatment (mean, 22.2 days vs. 48.3 days) compared with controls.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…41 Patient navigation can be especially helpful in support for education and lifestyle changes in survivorship care and improved health-related quality of life. 39 Gabitova et al 25 showed, in a northern California safety net hospital, that patient navigation increased collaboration between patients and providers and facilitated better understanding of their care process. The implementation of a culturally tailored intervention to improve palliative care for Spanish-speaking patients in a study by Fink et al 42 had lay patient navigators address the concerns of patients and their families and reduce barriers to palliative care.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…While we found numerically higher HRQOL in the intervention arm, it was not statistically significant. Although patient navigation based intervention have shown improvement in some domains of HRQOL, 50 several prior studies results with SCP intervention have shown no improvement 2 or have shown even worsening of HRQOL. 51 We also assessed self-efficacy and found that self-efficacy was also not different in either of the arms, this is consistent with prior literature which has shown mixed results in self-efficacy with SCP.…”
Section: Discussionmentioning
confidence: 92%
“…33 In a prospective one-arm study assessing SCP and information provision in 62 childhood cancer survivors at increased risk for late effects, nearly half of those who had seen a physician since SCP receipt had shared it; most who had not seen a physician planned to share the SCP when they did. 34 Further, the investigators found that PCPs seemed too busy to be involved in the study or to utilize the resources offered to them directly, but they ordered tests when the survivor presented them with information on risks. In a study of 5,661 adult survivors of childhood cancer, Steele et al found that discussing cancer-related risks with a doctor is the strongest predictor of getting screened for late effects and that the physician's access to the survivor's cancer treatment summary significantly predicted screening for relevant health risks.…”
Section: Mechanism A2: Transfer Of Information To Pcpsmentioning
confidence: 99%